2022
DOI: 10.2147/jir.s347293
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-24-3p Mediates the Negative Regulation of Lipopolysaccharide-Induced Endometrial Inflammatory Response by Targeting TNF Receptor-Associated Factor 6 (TRAF6)

Abstract: Purpose Endometritis is a female reproductive disease that affects the cattle industries development and microRNAs (miRNAs) play a pivotal role and critical regulators of the innate immune response in varieties of diseases. The present study intends to investigate the regulatory role of miR‐24-3p in the innate immune response involved in endometritis and evaluate its therapeutic potential. Methods Whole mice uteri and bovine endometrial epithelial cells (BEECs) were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Similarly, we observed that the overexpression of miR-203b has a beneficial effect on metabolic homeostasis [ 39 ]. We have also found an increase in the expression of miR-21, miR-24-3p and miR-146-5p, which are involved in the activation of a pro-inflammatory macrophage phenotype and the attenuation of inflammation [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that the overexpression of miR-203b has a beneficial effect on metabolic homeostasis [ 39 ]. We have also found an increase in the expression of miR-21, miR-24-3p and miR-146-5p, which are involved in the activation of a pro-inflammatory macrophage phenotype and the attenuation of inflammation [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-24 expression decreases with cellular senescence [ 83 ], and it was defined as a mitochondrial miR (mitomiR) [ 84 ]. It was described that miR-24-3p and miR-124 attenuate the expression of pro-inflammatory mediators via NF-kB signaling [ 85 , 86 ]. miR-124 also increases in senescent skin, while it decreases during tumorigenesis, particularly in squamous cell carcinoma [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that Exo-derived miR-24-3p promotes M2 macrophage polarization [56,57]. Interestingly, previous studies have established that miR-24-3p plays a role in promoting in ammation recovery [58][59][60][61]. However, the speci c mechanisms by which miR-24-3p affects microglia and its potential contribution to pain relief remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%